Allergic respiratory diseases in Sri Lanka; the way forward - Malavige, N. (My University, 2016)
Attached

A sth m a, atopic dermatitis, allergic rhinitis, allergic conjunctivitis, food allergies, insect ve n om allergies and an ap h ylaxis are a significant c a u se o f m orbidity an d mortality in the world. T h e glob al burden o f allergy related d ise a se s h ave trebled in the last d e c a d e a n d are a lso o n the rise in low er m iddle incom e countries su c h a s Sri Lanka. A lle rgy is b e com ing a n im portant problem , not only d u e to the increase in prevalence, but a lso b e cau se prevalence o f se ve re allergies an d m ore com plex fo rm s of allergies affecting multiple sy ste m s are on the rise. Sensitization to m an y environm ental alle rge n s is the c a u se o f asth m a an d allergic rhinitis is approxim ately 8 0 % of the patients. In a stu dy d on e by u s in children with asthm a, at the L a d y R id g e w a y H ospital for children, 52.1 % of the patients w ere sensitized to at le ast o n e allergen w h e re a s 6 .9 9 % w ere sensitized to 3 or m ore allergens. 3 5 .7 % tested positive to h o u se d u st mite, 2 5 .9 % to cockro ach a n d 5 .6 % to the indoor m oulds, 1 2 .6 % to cats an d 9.1 % to d o gs. T h o se with daily sy m p to m s h ad a h igher rate o f sensitization to a n allergen than th o se who h ad w eekly or se a so n a l sym p to m s. Sensitization rates to c o m m o n ae roalle rge n s w ere h igher in adult patients suffering from severe form s of asthm a. Until recently, the d ia g n o sis of allergic bronchopulm onary a sp e rgillo sis in m any patients could not be confirm ed d u e to lack of d iagn ostic tests. How ever, m a n y of our patients with allergic asth m a an d allergic rhinitis, only receive sym ptom atic treatm ent an d are not offered im m unotherapy, w hich can potentially cure them . Although im m unotherapy for allergen desensitization in ve n om allergy, asth m a an d allergic rhinitis, is standard practice in m an y developed countries, in S ri L a n k a w e la g far behind. i W e can be very proud of our achievem ent in prim ary health care an d in com b atin g an d eradicating m any com m u nicab le d ise a se s. How ever, the epidem iological patterns of d ise a se s h ave now ch a n g e d with d ise a se s due to allergies increasingly becom ing com m on. Therefore, in order to m eet these challenges, it w ould be crucial to im prove education a n d training in the a lle rgie s an d introducing ‘novel’ treatm ent m odalities su c h a s immunotherapy.